Gestión de recursos hídricos en América Latina: Un asunto de equidad y sostenibilidad (2019)
Basic services privatization policies began to be adopted from the 80s in developed countries (from Europe, North America, and Asia) as well as in developing countries. As a result, changes in policies and norms which govern water management were implemented, in order to reduce or eliminate regulation of water and drainage service supply industry, thus facilitating an active participation of the private sector in water utility services. This has been done to create favorable conditions for both the use of instruments and market, intending to reduce social equity problems in terms of access to water resources. This article has as its main purpose to show a general overview of water markets and water privatization in Latin America, as well as the consequences of such a practice in terms of social equity. The article shows empirical evidence of water markets in Latin America, which is then compared with the assumptions of some economists who argue that privatization does not go against social equity in terms of low-income community access to natural resources.